2001
DOI: 10.1590/s0102-35862001000100007
|View full text |Cite
|
Sign up to set email alerts
|

Resposta a broncodilatador na espirometria: que parâmetros e valores são clinicamente relevantes em doenças obstrutivas?

Abstract: Respostas estatísticas dos parâmetros funcionais são largamente utilizadas após administração de broncodilatador (Bd) nos laboratórios de função pulmonar em doenças com obstrução ao fluxo aéreo. Sua relevância clínica é discutível. Objetivo: Determinar que parâmetros espirométricos refletem a melhora na tolerância ao exercício e na dispnéia em resposta a broncodilatador em doenças pulmonares obstrutivas. Métodos: 50 pacientes com DPOC e/ou asma (VEF 1 /CVF = 41 ± 11%) realizaram manobras de CV lenta e forçada,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 59 publications
(100 reference statements)
1
21
0
3
Order By: Relevance
“…In a previous study, in which the BHT max V EI was sequentially measured in the postoperative period, the authors reported that the test was easy to perform, was well accepted by patients, and was an interesting tool to be used in the clinical follow-up of patients in the postoperative period, having aided in detecting complications during that period. (22)(23)(24)(25)(26) However, that study did not evaluate the role of bronchodilator use in the BHT max V EI .…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, in which the BHT max V EI was sequentially measured in the postoperative period, the authors reported that the test was easy to perform, was well accepted by patients, and was an interesting tool to be used in the clinical follow-up of patients in the postoperative period, having aided in detecting complications during that period. (22)(23)(24)(25)(26) However, that study did not evaluate the role of bronchodilator use in the BHT max V EI .…”
Section: Discussionmentioning
confidence: 99%
“…(5,15,27) Some authors have reported that patients with COPD develop progressive air trapping upon exertion without altering total lung capacity, presenting increased functional residual capacity and decreased IC. (28)(29) By reducing this dynamic hyperinflation, bronchodilator use can increase IC and decrease the functional residual capacity.…”
Section: Discussionmentioning
confidence: 99%
“…(2)(3) Although some studies showed poor response to bronchodilators in FEV1 in patients with COPD, these drugs have always been the main therapeutic resource used to combat this illness and are widely prescribed. (2)(3)(4)(5) The functional limitation in patients with COPD, classically determined through the measurement of FEV 1 , correlates well with limited exercise tolerance, ability to perform day-to-day activities, severity of dyspnea and lower quality of life. Spirometry, and FEV 1 in particular, is a good marker for the staging of the disease.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations